Comparison of methods of evaluation of the financial structure in selected industry and countries - Nicole Škuláňová; Veronika Šudová (Trends Economics and Management, 2022)
Purpose of the article: The issue of capital or financial structure is still a very current topic, the beginning of which dates back to the middle of the last century. Despite such a long time, there is still no universal theory that would help us understand the behaviour of companies in this area. This is due to the fact that each industry, sector, economy, and even the company itself has a different strategy, and therefore a different financial structure. Unfortunately, it is not possible for researchers to analyse all the companies in the world individually, but it is at least possible to examine individual industries and economies. The purpose of this research is to expand knowledge about the financial structure in the industry - Accommodation and Food Service activities in 8 selected countries of Central and Eastern Europe during the period 2010-2018. A total of 23,991 companies are analysed, which are divided into medium and large. Due to the fact that research in this industry in selected economies was not found, this research could significantly expand knowledge about the financial structure in selected economies and the sizes of companies individually.Methodology/methods: Two methods were chosen to meet the aim - the least squares method and the Generalized Method of Moments. It is a comparison of two regression analyses, a simple one, in which several assumptions must be met, and a modified one, in which only one test follows to verify the credibility of the resulting model.Scientific aim: The aim of this research is to determine whether profitability, liquidity, asset structure, non-debt tax shield, the GDP growth rate, inflation rate, and reference interest rate affect the level of total, long-term and short-term debt.Findings: The main finding of the research is the limitation in the use of the least squares method in terms of fulfilling the basic assumptions and the fact that both internal and external determinants have an influence on the formation of financial structure, however, in terms of significance, the influence of external determinants clearly prevails.Conclusions: The main conclusion is that non-corporate determinants have the most significant impact on the level of indebtedness, with the influence of the reference interest rate clearly dominating in terms of the value of coefficients; while in terms of the frequency of coefficients the GDP growth rate is significant.
Keywords: G30; G32; 650; Financial structure; profitability; liquidity; non-debt tax shield; asset structure; GDP; inflation; interest rate